Albert Einstein and Quantum Physics - Dionisio, Paulo Henrrique (2005)
The paper "On a heuristic point of view concerning the production and transformation of light" published by Albert Einstein in 1905 is discussed. It is shown that Einstein proposed a different and independent solution to the problem of blackbody radiation from the one presented by Max Planck in 1900, thus beginning Quantum Physics for the second time. The present work intends to contribute for the knowledge of the work of Albert Einstein in its whole extension, so that its meaning and consequences for the modern world could be fully recognized and evaluated. It is suggested, in addition, a small modification concerning the presentation of the concept of photons in modern physics classes.